Peligrosidad criminal e individualización judicial de la pena - Borja Jiménez, Emiliano (Nuevo foro penal, 2016)
Any criminal system gives the judge some discretion to impose the sentence the convicted offender. Sometimes the defendant revealed that he will continue committing crimes in the future. The response of the law in these cases is often the imposition of aTodo sistema penal otorga al juzgador cierto arbitrio para imponer la pena al reo declarado culpable. En ocasiones ese reo revela en el hecho enjuiciado que va a seguir delinquiendo en el futuro. La respuesta del ordenamiento jurídico en estos casos suel